Cysteamine–bicalutamide combination therapy corrects proximal tubule phenotype in cystinosis. Issue 7 (24th June 2021) - Jamalpoor, Amer; van Gelder, Charlotte AGH; Yousef Yengej, Fjodor A; Zaal, Esther A; Berlingerio, Sante P; Veys, Koenraad R; Pou Casellas, Carla; Voskuil, Koen; Essa, Khaled; Ammerlaan, Carola ME; Rega, Laura Rita; van der Welle, Reini EN; et al.
Abstract: Nephropathic cystinosis is a severe monogenic kidney disorder caused by mutations in CTNS, encoding the lysosomal transporter cystinosin, resulting in lysosomal cystine accumulation. The sole treatment, cysteamine, slows down the disease progression, but does not correct the established renal proximal tubulopathy. Here, we developed a new therapeutic strategy by applying omics to expand our knowledge on the complexity of the disease and prioritize drug targets in cystinosis. We identified alpha‐ketoglutarate as a potential metabolite to bridge cystinosin loss to autophagy, apoptosis and kidney proximal tubule impairment in cystinosis. This insight combined with a drug screen revealed a bicalutamide–cysteamine combination treatment as a novel dual‐target pharmacological approach for the phenotypical correction of cystinotic kidney proximal tubule cells, patient‐derived kidney tubuloids and cystinotic zebrafish. SYNOPSIS: Nephropathic cystinosis is a severe genetic disorder caused by mutations in the lysosomal cystine transporter, cystinosin. Although several cellular defects have been associated with cystinosis, the mechanism linking cystinosin loss, and epithelial dysfunction remains largely unknown. CRISPR‐generated isogenic cystinotic renal proximal tubule cells recapitulate the disease pathology and allow direct evaluation of the effect of cystinosin loss, independent of chronic exposure to disease‐related changes in the body. Alpha‐ketoglutarate (αKG), an important intermediate of the tricarboxylic acid cycle, is a part of a unifying mechanism linking cystinosin loss, lysosomal autophagy disruption and proximal tubule impairment in cystinotic renal proximal tubule cells. Cysteamine‐bicalutamide combination therapy restores proximal tubule function in advanced in vitro models and corrects cystinosis related defects in cystinotic zebrafish. Our findings demonstrate that the combination therapy is a novel potential treatment for patients with nephropathic cystinosis. Abstract : Nephropathic cystinosis is a severe genetic disorder caused by mutations in the lysosomal cystine transporter, cystinosin. Although several cellular defects have been associated with cystinosis, the mechanism linking cystinosin loss, and epithelial dysfunction remains largely unknown.